Implementation Of West Kalimantan Regional Police Policy In Effectiving Forest And Land Fire Law Enforcement Efforts - Hidayat, Fanni Athar; Kurniawan, Teguh (Universitas Muhammadiyah Sumatera Utara, 2024)
Cases of forest and land fires are an environmental problem tha never ends every year. The number of forest and land fires in Indonesia is a special concern for law enforcers to continue collaborating in creating synergistic handling policies between each law enforcement agency to resolve and prevent forest fire cases especially in the West Kalimantan region. The West Kalimantan Regiononal Police, based on Circulatar Letter Number SE/15/XI/2016, is makin every effort to deploy police personnel to assist in handling and enforcing the law on forest fire cases in The West Kalimantan Jurisdiction. This is because the still alive and developing culture of burning areas of land by customary law commnities means there is a need for law enforcement, in accordance with standards and operations so that forest and land fires can be minimized. And it is necessary to use the implementation of Georgre Edward III’s Theory which prioritizes aspects of communication, completeness of natural resources, disposition, and reffering to SOPs to enforce cases of forest and land fires in West Kalimantan